Implementation of an IoT-Based Smart Health Mirror to Enhance Community Health Awareness at Posyandu Cempaka, Pagelaran Village - Aas Saádah; Yuli Wahyuni; Nyayu Siti Aminah Lily Elfrieda (Pascasarjana Universitas Mataram, 2026)
Community health is a crucial aspect of improving quality of life, particularly through the role of Posyandu (Integrated Health Service Post) as a primary healthcare service at the village level. However, low public awareness of conducting independent health check-ups remains a significant challenge, especially in areas with limited facilities and digital literacy. This community engagement program aimed to enhance community health awareness through the implementation of an Internet of Things (IoT)-based Smart Health Mirror at Posyandu Cempaka RW 05, Pagelaran Village. The implementation methods included socialization activities, cadre training, technology deployment, and evaluation using a pre-test and post-test approach, followed by a three-month monitoring and mentoring phase. The results indicated an improvement in community health literacy, with the average score increasing from 62.4 (pre-test) to 81.7 (post-test), representing a 31% improvement. The implementation of the Smart Health Mirror also encouraged greater community participation in self-health monitoring and strengthened the function of Posyandu as a technology-supported health service center. Overall, this program contributed to improving the quality of community health services and has the potential to be replicated in other Posyandu as a model for technology-based community engagement initiatives.